The Men in the Life and Work of Olga Kirsch - Roth, Egonne (Werkwinkel, 2014)
Olga Kirsch’s life and work was dominated by three men: her father Schmuel M. Kirsch, her youth lover Ellis, and her husband Joseph Gillis. Their presence can be felt throughout her oeuvre, both in her published Afrikaans and in her unpublished English poetry culminating in a collection of seventy-seven poems written in the months that followed the death of her husband. Through these poems the reader is introduced to a passionate side of Kirsch’s personality that was rarely seen by those who knew her in the normal course of her life. These three relationships resulted in some of Kirsch’s most beautiful poetry, of which her “Vyf sonnette vir my vader” is probably the best known.